Effects of arbuscular mycorrhizal fungi on plant growth and herbivore infestation depend on availability of soil water and nutrients - Wang, Minggang; Wang, Zhongbin; Guo, Mingjie; Qu, Laiye; Biere, Arjen (Frontiers in Plant Science, 2023)
Fitness of plants are affected by their symbiotic interactions with arbuscular mycorrhizal fungi (AMF), and such effects are highly dependent on the environmental context. In the current study, we inoculated the nursery shrub species Artemisia ordosica with AMF species Funneliformis mosseae under contrasting levels of soil water and nutrients (diammonium phosphate fertilization), to assess their effects on plant growth, physiology and natural infestation by herbivores. Overall, plant biomass was synergistically enhanced by increasing soil water and soil nutrient levels. However, plant height was surprisingly repressed by AMF inoculation, but only under low water conditions. Similarly, plant biomass was also reduced by AMF but only under low water and nutrient conditions. Furthermore, AMF significantly reduced leaf phosphorus levels, that were strongly enhanced under high nutrient conditions, but had only minor effects on leaf chlorophyll and proline levels. Under low water and nutrient conditions, specific root length was enhanced, but average root diameter was decreased by AMF inoculation. The negative effects of AMF on plant growth at low water and nutrient levels may indicate that under these conditions AMF inoculation does not strongly contribute to nutrient and water acquisition. On the contrary, the AMF might have suppressed the direct pathway of water and nutrient absorption by the plant roots themselves despite low levels of mycorrhizal colonization. AMF inoculation reduced the abundance of the foliar herbivore Chrysolina aeruginosa on plants that had been grown on the low nutrient soil, but not on high nutrient soil. Fertilization enhanced the abundance of this herbivore but only in plants that had received the high water treatment. The lower abundance of the herbivore on AMF plants could be related to their decreased leaf P content. In conclusion, our results indicate that AMF negatively affect the growth of Artemisia ordosica but makes them less attractive to a dominant herbivore. Our study highlights that plant responses to AMF depend not only on the environmental context, but the direction of the responses can differ for different components of plant performance (growth vs. defense).